The impact of political instability in attracting foreign investment (Case of Albania) (European Journal of Social Science Education and Research, 2023)
The aim of this study is to define the impact of political instability on economic growth. Considering the multidimensionality of a factor like political instability, the study employs only four variables to measure it. The variables used to measure political instability are civil liberties, political rights, number of women in parliament and the government changes during years. Regarding the economic growth this study employs the variable of real GDP growth rate as the best factor indicating economic growth. The data are obtained from national and international sources like “INSTAT”, “Bank of Albania” and “The Global Economy”, and takes into consideration the period from 1990-2015. According to the literature it was expected to have a significant negative impact of political instability on economic growth. Through the results obtained from the econometric model the expectation holds. What is interesting is the insignificance of all explanatory variables beside the variable of civil liberty, which is found to be highly significant. The analysis reveals that an increase in civil liberties would have a positive impact on GDP growth rate. The study also concluded that the importance of civil liberties as a transmission channel of political instability can be justified with the weakness of the judicial system and the classification of Albania as a partly-free country. The comperative method was used in this study. The topics discussed and addressed are freedom and rights, their development over the years, women in politics, participation and increased representation, economic changes, crises and their causes and how it has evolved with democratic developments.